Changes in Membrane Receptors and Ion Channels as Potential Biomarkers for Osteoarthritis - Lewis, Rebecca; Barrett-Jolley, Richard (Frontiers in Physiology, 2015)
Osteoarthritis (OA), a degenerative joint condition, is currently difficult to detect early enough for any of the current treatment options to be successful. Significant joint damage usually occurs before patients present with pain. Early diagnosis of this disease could increase the numbers of patients who are able to slow its progression. There are now several diseases where membrane protein biomarkers are used for early diagnosis. A number of membrane proteins have been shown to change with OA but not enough is currently known about these to enable their use as biomarkers. Here, we summarise several ion channels, transporters and membrane receptors that have been shown to be changed in OA patients, and discuss the potential for membrane proteins use as biomarkers.